1983
DOI: 10.1002/pssb.2221200207
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Ga‐Doped α‐Al2O3 Crystals

Abstract: The introduction of Gas+ ions into cc-Al,O, crystals results in a new complex luminescence band at about 5 eV. The main optjcal excitation maximum is observed a t 8.5 eV indicating the bound exciton nature of the excited state. I n the cathodoluminescence spectra a t 80 K three sub-bands can be detected with maxima at 4.61, 5.15, and 6.58 eV. The luminescence decay in all the three bands has two exponential components -a short one with T = (15 & 1) ns and a long one with T about 1 4 s . The Ga-related luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The same interpretation has been used to explain emission properties of rare-earth doped oxides [46]. With regard to Al 2 O 3 the idea on the formation of a bound exciton at impurity ions has been proposed even earlier by Jansons et al [47] in their studies of Ga-doped Al 2 O 3 . Later, when analysing the excitation spectra of Ga-and Scdoped Al 2 O 3 Lushchik et al [48] reported that impurity emission can be excited efficiently below the 8.8 eV band.…”
Section: Article In Pressmentioning
confidence: 84%
“…The same interpretation has been used to explain emission properties of rare-earth doped oxides [46]. With regard to Al 2 O 3 the idea on the formation of a bound exciton at impurity ions has been proposed even earlier by Jansons et al [47] in their studies of Ga-doped Al 2 O 3 . Later, when analysing the excitation spectra of Ga-and Scdoped Al 2 O 3 Lushchik et al [48] reported that impurity emission can be excited efficiently below the 8.8 eV band.…”
Section: Article In Pressmentioning
confidence: 84%
“…In addition, the electronic structures also change after the substitution of the Al atoms by the Fe atoms on the surface. Except for the incorporation of Fe into the alumina surface, the B and Ga atoms, which are often used as the trivalent substitution ions for the zeolites [15,16], are also used in experiments for the preparation of high performance catalysis and semiconductors [8,9,[17][18][19]. Kibar et al prepared nanostructured boron doped alumina catalyst support [20] and found that the morphology of the supports can be modified from cracked surface to nanosphere formation by the introduction of boron.…”
Section: +mentioning
confidence: 99%
“…Kibar et al prepared nanostructured boron doped alumina catalyst support [20] and found that the morphology of the supports can be modified from cracked surface to nanosphere formation by the introduction of boron. Jansons [19]. The Garelated luminescence can be observed under the excitation of X-rays up to 600 K. In order to know the energies as well as the structures of the B and Ga incorporated -alumina surface at molecular level, the present work investigated the thermodynamic and structure properties of the B and Ga incorporated -alumina surface using dispersion corrected periodic density functional theory.…”
Section: +mentioning
confidence: 99%
“…Boehmite (g-AlOOH), a principal oxohydroxide of aluminium, is a crucial precursor in solgel technique for preparing high-purity and high-strength monolithic a-alumina ceramics for use as substrates for electronic circuits, abrasive grains, high-temperature refractory materials, fibres and thin films [10]. Boehmite 1D nanostructures can be used as molecular building units in the preparation of core/shell materials [1,[5][6][7][8][9]. Also, since the resulting alumina prepared from boehmite can keep the original size and morphology after calcination, great effort has been devoted to the investigation of nanoscale boehmite materials, especially 1D nanostructures, such as nanofibres and nanotubes [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high surface area, chemical and thermally stable properties and mesoporous properties, alumina has been extensively used as carrier and support for a variety of industrial catalysts at high-temperature as well as low temperatures. Alumina can be employed as a catalyst, adsorbent, composite materials and ceramics [1,[5][6][7][8][9]. Boehmite (g-AlOOH), a principal oxohydroxide of aluminium, is a crucial precursor in solgel technique for preparing high-purity and high-strength monolithic a-alumina ceramics for use as substrates for electronic circuits, abrasive grains, high-temperature refractory materials, fibres and thin films [10].…”
Section: Introductionmentioning
confidence: 99%